QARAQALPAQSTAN RESPUBLIKASÍNDA ALKALOIDLÍ ÓSIMLIKLERDIŃ TARQALÍWÍ - Temirbekov, Orazımbet (SCIENCE and SOCIETY, 2026)
The article describes the total number of species of alcaloid plants growing in the flora of the Republic of Karakalpakstan, as well as their distribution in botanical and geographical areas